Effect of Shot Peening Parameters on PLA Parts Manufactured with Fused Deposition Modeling - Herianto, Herianto; Mastrisiswadi, Hasan; Nasution, Andri; Atsani, Sarah Iftin (Journal of Engineering and Technological Sciences, 2023)
Fused deposition modeling (FDM) is a technology with potential benefits such as material versatility, user-friendliness, and cost-effectiveness. However, the mechanical properties of FDM-printed specimens are relatively low. To address this issue, post-processing techniques such as shot peening can be employed. Shot peening is utilized as a post-treatment for metal-based and ABS materials, but its application to PLA material has not been explored yet. This study aimed to evaluate the effect of shot peening on the mechanical properties of FDM-printed PLA samples. A full factorial experimental design was employed with shot peening speed, duration, and number of outer shells as parameters. The tensile strength of 72 samples after the shot peening process was measured and evaluated. Analysis of variance (ANOVA) revealed that all parameters had a significant influence on tensile strength. Additionally, the interaction of speed*time and speed*number of shells also had a significant influence. Meanwhile, the interaction of time*number of shells and speed*time*number of shells had no significant influence. The findings of this study demonstrate the potential of post-processing techniques to enhance the mechanical strength of FDM components, particularly those composed of PLA material.